Writing fluency and quality in kindergarten and first grade: The role of attention, reading, transcription, and oral language - Kent, Shawn (2013)
In the present study, we examined the influence of kindergarten component skills on writing outcomes, both concurrently and longitudinally to first grade. Using data from 265 students, we investigated a model of writing development including attention regulation along with students’ reading, spelling, handwriting fluency, and oral language component skills. Results from structural equation modeling demonstrated that a model including attention was better fitting than a model with only language and literacy factors. Attention, a higher-order literacy factor related to reading and spelling proficiency, and automaticity in letter-writing were uniquely and positively related to compositional fluency in kindergarten. Attention and higher-order literacy factor were predictive of both composition quality and fluency in first grade, while oral language showed unique relations with first grade writing quality. Implications for writing development and instruction are discussed.